Effect of Cassava-Legume Intercropping Systems on the Population Dynamics of Legumes Insect Pests in Three Major Agro-Climatic Zones of Sierra Leone - Mansaray, Augustine; Karim, Abdul Babatunde; Yormah, Thomas Brima Rick; Conteh, Abdul Rahman (International Research Journal of Insect Sciences, 2022)
Field trials were conducted in three agro-climatic zones of the country to evaluate the effect of cassava-legume-based intercropping systems on the population dynamics of legumes insect pests. The experiment consisted of a factorial treatment combination of seven cropping systems, two cassava architectures, and two spatial arrangements. The study reveals that a higher percentage incidence and severity scores of the legumes insect pests were recorded on the sole legumes compared to the intercropping systems. Also, intercropping the grain legumes using the erect cassava variety at a spatial arrangement of 1 m x 1 m recorded the lowest number of pests per plant, incidence and severity of legumes insect pests compared to the branched cassava architecture, and the 2 m x 0.5 m spatial arrangement. In conclusion, it was shown that, cassava-legume intercropping systems could significantly influence reduction in the number of pests per plant, incidence, and severity of legumes insect pests.